Kaspersky Labs unveils new version of anti-virus software for Unix/Linux (Worldwide computer products news, 2001)
Worldwide Computer Products News-18 July 2001-Kaspersky Labs unveils new version of anti-virus software for Unix/Linux (C)1995- 2001 M2 COMMUNICATIONS LTD http://www.m2.com The data-security software developer Kaspersky Labs has released the latest version of its Kaspersky Anti-Virus product for the Unix/Linux operating systems.